Unilateral ischemic central retinal vein occlusion in a young healthy adult: a case report - Mohd Amin, Muhammad Hafiz As-Shaarani; Rosli, Abdul Hadi; Salam, Adzura (2021)
Central retinal vein occlusion (CRVO) is an obstruction of central retinal vein due to the impingement from the fellow central retinal artery. It is the second most common retinal vascular disease after diabetic retinopathy. Risk factor of CRVO includes diabetes mellitus, hypertension, hyperlipidemia, cardiovascular disease, male gender and age above 50 years; with 90% of the cases occurred in individual aged 55 years and above. We report a rare case of left eye ischemic CRVO in a 24-year-old healthy gentleman who later on found out to have hypercholesterolemia. He presented with a sudden onset of reduced vision of his left eye. Examination revealed visual acuity (VA) of the left eye was 6/120. Fundus examination showed marked papilloedema with dilated and tortuous blood vessels and extensive flame-shaped hemorrhages with cotton wool spots in all four retinal quadrants. There was a presence of macular edema as well. The ancillary tests confirmed the diagnosis of left eye ischemic CRVO with significant macular edema. The blood investigation revealed elevated cholesterol levels. For treatment, 6 times of monthly intravitreal Ranibizumab injections were planned for the macular edema and oral Atorvastatin 40 milligrams daily was started. Following the intravitreal Ranibizumab injection, his VA has significantly improved with a reduction of macular edema. This report highlights the importance of prompt diagnosis and investigation of CRVO, especially in the younger age group. Early treatment of macular edema secondary to CRVO is able to reduce the edema thus leads to VA improvement.